2020
DOI: 10.1177/0021934720946802
|View full text |Cite
|
Sign up to set email alerts
|

The Framing of Race: Trayvon Martin and the Black Lives Matter Movement

Abstract: This study analyzed two national newspapers to investigate how each framed race in coverage of Trayvon Martin and the Black Lives Matter movement. Drawing from Feagin’s white racial frame as the framework for analysis, results show that the news coverage reflected an encompassing pro-white/anti-black master-frame that presented Black Americans as inadequate, lawless, criminal, threatening and at times biologically different. Some news stories contributed to the media’s conceptualization of race within a libert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Recent studies have shown Black sources in media continue to be framed negatively as lawless and threatening, while white sources are framed positively and portrayed as virtuous protectors. Lane et al (2020) found two national newspapers utilized these persistent frames in their coverage of the killing of Trayvon Martin in 2012 and the early days of the BLM movement. They argued the use of pro-White/anti-Black frames drew attention away from issues of racial profiling and police violence toward Black Americans, perpetuating a narrative of liberty for White men and justice against Black men.…”
Section: Media Framing Theory and The Protest Paradigmmentioning
confidence: 99%
“…Recent studies have shown Black sources in media continue to be framed negatively as lawless and threatening, while white sources are framed positively and portrayed as virtuous protectors. Lane et al (2020) found two national newspapers utilized these persistent frames in their coverage of the killing of Trayvon Martin in 2012 and the early days of the BLM movement. They argued the use of pro-White/anti-Black frames drew attention away from issues of racial profiling and police violence toward Black Americans, perpetuating a narrative of liberty for White men and justice against Black men.…”
Section: Media Framing Theory and The Protest Paradigmmentioning
confidence: 99%
“…For example, the concern one of the men made about contracting a disease might be heightened due to the COVID-19 pandemic. The concern about rioting in a rural location might not have been prevalent if there was not very adversarial news coverage of rioting over the spring and summer of 2020 (Lane et al, 2020). However, due to the physical demands of the job and how they necessitate retirement once a certain physical decline occurs (Kirlin et al, 2017), the concerns of conflicts between older vs younger firefighters are expected to be an argument in perpetuity in the field.…”
Section: Limitationsmentioning
confidence: 99%
“…Media priming and its effects on public opinion is also found in studies about racial representation of African American communities in media, including, but not limited to discourses of police brutality as well as the Black Lives Matter movement. Such studies show that media framing can build a sense of hostility towards African American communities through repetition of negative image-building (Kulaszewics, 2016;Lane et al, 2020). In the same context, a study by Fridkin et al (2017) showed that there is a tendency for media framing to oscillate between angles of sympathetic reporting which underlines human interest or the contrasting angle of establishing law and order through the perspective of authorities.…”
Section: Ethnic Minoritiesmentioning
confidence: 99%